ANALISIS KESULITAN BELAJAR PEMECAHAN MASALAH MATEMATIKA MATERI KPK DAN FPB KELAS IV SD - Yayuk Lukita Sari; Ervina Eka Subekti; M Yusuf Setia Wardana (Universitas Negeri Medan, 2020)
Abstract : Analysis of Learning Difficulties in Solving Mathematic Probrems in KPK and FPB Grade IV Elementari School. This study aims to describe the types of learning difficulties and the factors that influence learning difficulties in solving mathematical problems in the form of story problems. This type of research is descriptive qualitative. The subjects of the study were 24 fourth grade students of Randuagung State Elementary School 02 Rembang. The instruments used were questions, interviews, documentation, questionnaires, and observations. The results obtained in this study are: (a) Difficulties in learning mathematical problem solving in the KPK and FPB material, including difficulties in understanding problems, formulating plans, implementing plans. and check again. (b) Factors that influence learning difficulties mathematics problem solving in the KPK and FPB material include attitude factors, family environment factors, and school environment. Keywords: learning difficulties, mathematical problem solving. Abstrak : Analisis Kesulitan Belajar Pemecahan Masalah Matematika Materi KPK dan FPB Kelas IV SD. Penelitian ini bertujuan untuk mendeskripsikan jenis kesulitan belajar dan faktor-faktor yang mempengaruhi kesulitan belajar dalam memecahkan masalah matematika berbentuk soal cerita. Jenis penelitian ini adalah deskriptif kualitatif. Subjek penelitian adalah 24 siswa kelas IV Sekolah Dasar Negeri Randuagung Rembang. Instrumen yang digunakan berupa soal, wawancara, dokumentasi, angket, dan observasi. Hasil yang diperoleh dalam penelitian ini adalah : (a) Kesulitan belajar pemecahan masalah matematika materi KPK dan FPB termasuk kesulitan dalam memahami masalah, merumuskan rencana, melaksanakan rencana. dan memeriksa kembali. (b) Faktor yang mempengaruhi kesulitan belajar pemecahan masalah matematika materi KPK dan FPB meliputi faktor sikap, faktor lingkungan keluarga, dan lingkungan sekolah. Kata kunci:, kesulitan belajar, pemecahan masalah matematika.